A Review Of Second Language Teaching And Learning Through Short Fiction And Communicative Approach - Dr. Tariq Khan (University of Chitral Journal of Linguistics and Literature, 2019)
This paper examines the potential role of literature and Communicative Approachin teaching second language (SL). This paper mainly focuses on digging out theprospective role of literature and Communicative Approach in teaching SL.Analysis of past studies indicate that teacher usually recourse to GrammarTranslation Method for teaching of English language, for this method needs littleendeavor and supplementary materials[1]. The reviewed literature has found thatthis method is ineffective and futile. To critically examine the potential role ofliterature in combination with Communicative Approach in teaching SL, thispaper tries to unearth the current literature and investigates the relevant researchworks carried out on the importance of exploiting Literature and CommunicativeApproach for teaching of English language. The present paper found that usingliterature and communicative approach for teaching of SL is more effective andproductive than GTM. In the light of findings of this study, it is recommendedthat teachers of L2 need to exploit literature and employ CommunicativeApproach for teaching of second language.